2007
DOI: 10.1161/01.atv.0000258945.76141.8a
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of a Retinoid X Receptor γ Gene Variant in Familial Combined Hyperlipidemia That Associates With Atherogenic Dyslipidemia

Abstract: Objective-The genetic background of familial combined hyperlipidemia (FCHL) has not been fully clarified. Because several nuclear receptors play pivotal roles in lipid metabolism, we tested the hypothesis that genetic variants of nuclear receptors contribute to FCHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
2
10
1
1
Order By: Relevance
“…CD163 antigen, a member of the scavenger receptor cysteine-rich (SRCR) super family class B [32], distal-less homeobox 5 (DLX5) responsible for proliferation of tumor cells [33] and insulin-like growth factor binding protein 5 (IGFBP5) isoform 2 found in breast cancer [34] were also identified in ALC formation. Thyroid hormone-responsive protein (THRSP) previously reported in adipogenesis [35,36] and retinoic acid receptor RXR-gamma associated with familial combined hyperlipidemia [37] were identified during adipogenesis. FABP4 and CD36 which encode lipid transporters [38,39] were up-regulated in all tissues.…”
Section: Discussionmentioning
confidence: 99%
“…CD163 antigen, a member of the scavenger receptor cysteine-rich (SRCR) super family class B [32], distal-less homeobox 5 (DLX5) responsible for proliferation of tumor cells [33] and insulin-like growth factor binding protein 5 (IGFBP5) isoform 2 found in breast cancer [34] were also identified in ALC formation. Thyroid hormone-responsive protein (THRSP) previously reported in adipogenesis [35,36] and retinoic acid receptor RXR-gamma associated with familial combined hyperlipidemia [37] were identified during adipogenesis. FABP4 and CD36 which encode lipid transporters [38,39] were up-regulated in all tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Pparg has been implicated in atherosclerosis (36), coronary heart disease (37) and hypertension (38). RXRs are members of the NR2B family of nuclear receptors and are major heterodimerization partners of PPARs (39). RXRs are involved in mediating the anti-proliferative effects of retinoic acid, which can comprise a collection of molecules with retinoids to maintain homeostasis in adults (40).…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have reported the role of RXRs and PPARs in controlling cellular metabolism in tissues, including the myocardium (40,41). Nohara et al (39) suggested that a variant of Rxrg contributes to human genetic dyslipidemia. Taken together, the TFs, Pparg and Rxrg, may have utility in the diagnose and treatment of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…FCHL family members exhibit varying degrees of dyslipidemia with either isolated high triglycerides, LDL cholesterol, or both, which is another feature of FCHL. Several candidate genes have been reported, such as upstream stimulatory factor 1 (USF1) 21) , apoA5 22) , Retinoid X receptor- 23) , hepatic lipase 24) , and so forth. The diagnostic criteria for FCHL in Japan are as follows:…”
Section: Familial Combined Hyperlipidemia (Fchl)mentioning
confidence: 99%